Lymphatic-immune interactions in the musculoskeletal system - Liu, Hanyu; Liu, Lu; Zhang, Yuheng; Tian, Qi; Ding, Zhangfan; Chen, Junyu; Kusumbe, Anjali P. (Frontiers in Immunology, 2025)
Traditionally, the role of lymphatic vessels has been understood as primarily involving fluid transport and immune surveillance. In addition to these roles, recent studies have revealed a paracrine function of lymphatics through the dissemination of inductive factors, known as lymphangiocrine signals including in musculoskeletal physiology and diseases. These signals play diverse roles, including maintaining tissue equilibrium and facilitating regeneration. Impaired lymphangiocrine signaling and lymphatic function are features of musculoskeletal diseases. This review summarizes dysregulation of lymphatic vessels and interactions with immune cells during musculoskeletal diseases. Further, this review provides insights into lymphangiocrine signals as a potential therapeutic target.